Assessment of the possibility of heavy metals elution from municipal solid waste incineration bottom ash into the soil and water - Katarzyna Godyń; Barbara Dutka; Czesława Rosik-Dulewska; Tomasz Ciesielczuk; Mariusz Głowacki (Desalination and Water Treatment, 2025)
The aim of the study was to assess the impact of different granulometric fractions of municipal solid waste incineration bottom ash (MSWI-bottom ash) on the soil and groundwater environment by determining the mobility of Zn, Cu, Pb, Cd, Cr, Ni, Co, Mn and Fe using various chemical methods. The reference method was the modified Tessier sequential extraction procedure, while complementary methods included extraction with aqua regia (AR) and deionized water. The post-process material was separated into granulometric fractions of different particle size intervals by dry sieving without crushing. Tessier sequential extraction, combined with X-ray fluorescence spectroscopy (XRF), enabled the assessment of the environmental impact of the individual granulometric fractions separated from bottom ash. The AAS method was used to determine the content of aqua regia-extractable metals of the individual granulometric fractions. The results obtained from Tessier sequential extraction (TSE) were compared with those from the other two methods (water, AR). Tessier extraction method showed that, metals concentrate mostly in Fractions III–V, except Cd where environmentally available fractions (F I – F III) exceed 80 % of its total content. Water extract show low leaching load with maximum 0.159 μg/kg in fraction < 0.025 mm. However Fe and Zn had the highest total concentrations, in case of water extracts Cu predominates with concentrations over 2 mg/kg in fractions below 0.063 mm what show risk of pollution of groundwater also with this element. From all analyzed granulometric fractions, high particles sample (2.5–4.0 mm) contain lowest amounts of all analyzed metals except Fe which exceed 22 g/kg, what was not observed in fine fractions.